Evaluative Analysis of Advertising Rental Value Policy in South Tangerang City: Impact and Implications - Ode, Irwan; Salam, Rahmat; ⁠Izzatusolekha (Global Writing Academica Researching & Publishing, 2024)
This study aims to evaluate the advertising rental value policy in South Tangerang City using six policy evaluation variables proposed by William N. Dunn, namely effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. This study uses qualitative-descriptive research. This research will be conducted at the Regional Revenue Agency (Bapenda) Office of South Tangerang City. This study consists of Primary Data through in-depth interview methods with stakeholders who have the authority to rent advertising and civil servants at Bapenda who are actively involved in the focus of the research study and Secondary Data obtained from external documents as secondary data. The results of this study indicate that this policy has been running quite well, although there are still obstacles in terms of supervision and socialization to the community. Suboptimal supervision has resulted in many illegal advertisements that have not been registered or have had their broadcast period extended. Public understanding of licensing procedures and tax obligations is still lacking, thus potentially reducing the optimization of regional tax revenues.